2018
DOI: 10.1016/j.ajhg.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assays Are Essential for Interpretation of Missense Variants Associated with Variable Expressivity

Abstract: Missense DNA variants have variable effects upon protein function. Consequently, interpreting their pathogenicity is challenging, especially when they are associated with disease variability. To determine the degree to which functional assays inform interpretation, we analyzed 48 CFTR missense variants associated with variable expressivity of cystic fibrosis (CF). We assessed function in a native isogenic context by evaluating CFTR mutants that were stably expressed in the genome of a human airway cell line de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 66 publications
5
80
0
Order By: Relevance
“…The above notwithstanding, to date, the actual scale of canonical 5′SSs capable of generating wild‐type transcripts in the case of GT>GC substitutions, both in the context of the frequency of such substitutions and the level of wild‐type transcripts generated by such substitutions, remains unknown owing to the intrinsic complexity of splicing (Boehm et al, ; De Conti, Baralle, & Buratti, ; Krainer, ; Wong et al, ; Zhang, Arias, Ke, & Chasin, ) and the lack of suitable model systems for study. This issue has important implications for medical genetics as mutant genotypes retaining even a small fraction of their normal function may differ significantly from null genotypes in terms of their associated clinical phenotypes (e.g., 5% normal CFTR gene expression is sufficient to prevent the lung manifestations of cystic fibrosis [Ramalho et al, ; Raraigh et al, ]; for hemophilia B and other coagulation factor deficiencies, raising plasma levels above 5% normal often results in milder bleeding phenotypes [Den Uijl et al, ; Scalet et al, ]). Herein, we attempted to address this issue by employing two distinct but complementary approaches in concert.…”
Section: Introductionmentioning
confidence: 99%
“…The above notwithstanding, to date, the actual scale of canonical 5′SSs capable of generating wild‐type transcripts in the case of GT>GC substitutions, both in the context of the frequency of such substitutions and the level of wild‐type transcripts generated by such substitutions, remains unknown owing to the intrinsic complexity of splicing (Boehm et al, ; De Conti, Baralle, & Buratti, ; Krainer, ; Wong et al, ; Zhang, Arias, Ke, & Chasin, ) and the lack of suitable model systems for study. This issue has important implications for medical genetics as mutant genotypes retaining even a small fraction of their normal function may differ significantly from null genotypes in terms of their associated clinical phenotypes (e.g., 5% normal CFTR gene expression is sufficient to prevent the lung manifestations of cystic fibrosis [Ramalho et al, ; Raraigh et al, ]; for hemophilia B and other coagulation factor deficiencies, raising plasma levels above 5% normal often results in milder bleeding phenotypes [Den Uijl et al, ; Scalet et al, ]). Herein, we attempted to address this issue by employing two distinct but complementary approaches in concert.…”
Section: Introductionmentioning
confidence: 99%
“…In silico prediction algorithms have been used to identify likely disease‐contributing CFTR variants, but the utility of predictive algorithms is controversial as they cannot differentiate between variants that caused severe, moderate, or minimal reduction in CFTR function . Our study similarly found inconsistent predictions as the algorithms predicted five variants to be deleterious but were annotated by CFTR2 as “non‐CF‐causing” (Table S1).…”
Section: Discussionmentioning
confidence: 81%
“…Studies in CF pig models have shown that CFTR function, and not the presence of chronic infection, leads to sinus hypoplasia, whereby older CF pigs spontaneously develop sinusitis regardless of infection 32 . Chloride conductance has been shown to accurately reflect CFTR function 20,21 and was used in this study. CFTR function, dichotomized to >1% or ≤1%, correlated with a history of surgical intervention for sinus disease.…”
Section: Discussionmentioning
confidence: 99%
“…CFTR genotype was determined from medical records or through molecular testing at the Johns Hopkins Diagnostic Laboratory. Functionality of CFTR missense or in‐frame deletion variants expected to produce protein was determined in vitro using heterologous expression systems in Fisher rat thyroid (FRT) or cystic fibrosis bronchial epithelial (CFBE) cell lines bearing individual variants 20,21 . Short‐circuit current was measured to assess chloride conductance from mutant CFTR and each variant was subsequently assigned a percentage of wild‐type CFTR function.…”
Section: Methodsmentioning
confidence: 99%